Socio-cultural Factors on The Establishment and Development of Communal Homestay in Eco Rural Tourism - Mita Erdiaty Takaendengan; Ricky Avenzora; Dudung Darusman; Cecep Kusmana (Institut Pertanian Bogor (IPB University), 2022)
Socio-cultural in homestay need to be identified, since such business can make very close interactions among tourists and rural life. This study aims to analyze socio-cultural factors in the establishment and development of communal homestays in the rural tourism. The study was conducted in tourist villages in three provinces, namely the Special Region of Yogyakarta (Brayut and Tanjung villages), West Java (Banceuy and Bunihayu villages) and North Sulawesi (Bahoi, Tiwoho, Popareng, Tandengan and Urongo villages). The research instrument used close ended questionnaire with 585 respondent. Data analysis was carried out in a quantitative descriptive by grouping, simplifying and presenting data using class intervals. The results showed that the majority of people in tourist villages agree on the concept of communal homestay which can be a forum for the preservation of the culture, customs and norms of the local community. In the aspect of cultural heritage conservation, homestay businesses are considered capable of providing the function of protecting and preserving customs, arts, culture, religious traditions and languages. The management of this communal homestay is considered to be able to create social interaction, cooperation and can reduce forms of unhealthy competition.